Development of an Augmented Reality-Based Digital Module For Islamic Religious Education Subjects - Supriadi; Vicky Bin Djusmin; Abdul Zahir (South Sulawesi Education Development (SSED), 2024)
This study aims to address the challenges in Islamic religious education, particularly the need for more engagement and interactivity in teaching Shalat procedures. The research developed an augmented reality (AR)–based digital module tailored for students at SDN 30 Matirowalie, utilizing the ADDIE development model. The module integrates 3D visualizations to enhance students' understanding and engagement. The research employed a mixed-methods approach, combining quantitative surveys and qualitative evaluations to assess the module's effectiveness. Data were collected from 30 students and validated by media and content experts. The analysis revealed that the AR module significantly improved student engagement and comprehension, with 95.34% of students responding positively. The module was rated